(untitled) (Progressive Agriculture, 2013)
An experiment was conducted at Jessore to observe the effect of planting date and variety on the yield of late planting tomato. The potentiality of fruiting in the late season were evaluated for BARI tomato 4, 5, 6 and 12 by planting December 01, December 16, January 01, January 16 and February 01. A combination of December 01 planting with BARI Tomato 5 variety performed better in respect of yield (57.07 t/ha). The variety BARI Tomato 5 also showed potential fruiting capability during late winter season and February 01 planting produced 11 ton/ha of potential yield. All the four varieties showed potential fruiting capability during late winter season and February 01 planting produced 4 6 tons of potential yield during late season. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16854 Progress. Agric. 20(1 & 2): 73 78, 2009